2005
DOI: 10.1128/ec.4.11.1794-1800.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-Independent Regulation of Protein Kinase A Substrate Phosphorylation by Kelch Repeat Proteins

Abstract: Pseudohyphal and invasive growth in the yeast Saccharomyces cerevisiae is regulated by the kelch repeatcontaining proteins Gpb1p and Gpb2p, which act downstream of the G protein ␣-subunit Gpa2p. Here we show that deletion of GPB1 and GPB2 causes increased haploid invasive growth in cells containing any one of the three protein kinase A (PKA) catalytic subunits, suggesting that Gpb1p and Gpb2p are able to inhibit each of these kinases. Cells containing gpb1⌬ gpb2⌬ mutations also display increased phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Also, although cAMP and glycogen oscillated when the cells were grown on glucose, no oscillation was observed in these metabolites when the cells were grown on ethanol media (38 and D.B.M., unpublished data). This finding does not rule out a role for the PKA pathway in controlling the respiratory oscillation because the TOR complex 1 and PKA signaling pathways cross-talk (39), and the PKA pathway can be phosphorylated independently of cAMP (40). The mechanistic elucidation of these transcriptional regulators is needed to elucidate their role during oscillatory dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Also, although cAMP and glycogen oscillated when the cells were grown on glucose, no oscillation was observed in these metabolites when the cells were grown on ethanol media (38 and D.B.M., unpublished data). This finding does not rule out a role for the PKA pathway in controlling the respiratory oscillation because the TOR complex 1 and PKA signaling pathways cross-talk (39), and the PKA pathway can be phosphorylated independently of cAMP (40). The mechanistic elucidation of these transcriptional regulators is needed to elucidate their role during oscillatory dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The kelch-repeat proteins interact with Gpa2 and contain seven kelch repeats that mimic the b propeller that is formed by seven WD-40 repeats in canonical G b subunits. Phenotypic analysis of gpb1D gpb2D double deletion mutants showed that the kelch-repeat proteins act as negative regulators of PKA signalling (Harashima and Heitman 2002;Batlle et al 2003;Lu and Hirsch 2005). Several mechanisms have been proposed to explain their effect.…”
Section: Regulation Of the Camp-pka Pathwaymentioning
confidence: 99%
“…Two kelchrepeat proteins, Gpb1 and Gbp2 (also known as Krh1 and Krh2), were proposed to function as the G␤ subunits for Gpa2 (34). However, further investigation has shown that these proteins are not G␤-mimics but instead function to inhibit signaling downstream of Gpa2 (21,(35)(36)(37). Using bioinformatic, genomic, biochemical, and pharmacological approaches we have identified Asc1 as the G␤ for Gpa2, and demonstrate a critical role for Asc1 in the glucose signaling pathway mediated by adenylyl cyclase.…”
mentioning
confidence: 99%